Penerapan Media Teka-Teki Silang Untuk Meningkatkan Berpikir Kritis Dalam Pembelajaran Akidah Akhlak Di Ma Ma’arif Assobariyyah Sukabumi - AF, Siti Suhasri; Nuryanah, Siti; Novianti, Nita; Rahayu, Silvia Sri; Septiani, Rina (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE APPLICATION OF CROSSWORD PUZZLE MEDIA TO IMPROVE CRITICAL THINKING IN LEARNING MORAL BELIEFS IN MA MA'ARIF ASSOBARIYYAH SUKABUMIThis research is motivated by the low critical thinking skills of students in Akidah Akhlak learning. The limitations of conventional teaching methods have resulted in a lack of student engagement in analytical thinking and problem-solving. Therefore, this study aims to enhance students' critical thinking skills through the application of Crossword Puzzle (TTS) media. The research employs a Classroom Action Research (CAR) method conducted in two cycles. The subjects of the study were tenth-grade students of MA Ma’arif Assobariyyah. Data were collected through tests and observations, then analyzed using descriptive statistics. The success indicators were determined based on the improvement in learning mastery and students' critical thinking skills. The results indicate a significant improvement in students' critical thinking skills and learning outcomes. In the first cycle, only 27.66% of students achieved mastery, while 72.34% had not yet met the required competency. After implementing improvements in the second cycle, the mastery rate increased to 93.62%, with only 6.38% of students remaining below the threshold. Additionally, students' engagement in analyzing questions, participating in discussions, and asking questions also showed significant improvement. The conclusion of this study is that the implementation of Crossword Puzzle media is effective in enhancing students' critical thinking skills and their understanding of the subject matter. This method can serve as an alternative strategy in teaching, encouraging students to be more active, think analytically, and significantly improve their learning outcomes.